Protective effects of salvianolic acid A on ischemic stroke: A meta-analysis of preclinical studies - Liu, An; Li, Wenjing; Zhang, Hangyao; Sun, Kexin; Xiao, Yuqian; Wan, Jun; Li, Pin; Wang, Yan; Hu, Sihan; Li, Yanjie; Bai, Yanjie (Frontiers in Pharmacology, 2025)
ObjectiveThe aim of this study was to investigate the protective effects of salvianolic acid A (SalA) on cerebral ischemic injury following ischemic stroke (IS) and its possible mechanisms, providing a scientific basis for future clinical research on IS.MethodsA comprehensive search was conducted across eight databases: PubMed, Embase, Web of Science, the Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang Database, VIP Database, and the China Biomedical Literature Database (CBM). The search included all literature from the establishment of each library up to February 2025. Data analysis was performed using STATA 15.0 software.ResultsA total of 15 studies involving 564 animals were included. The analysis showed that compared to the control group, SalA significantly reduced the infarct volume [SMD = −4.67, 95% CI = (−5.98, −3.36), and p < 0.001] and brain edema area [SMD = −5.291, 95% CI = (−7.607, −2.975), and p < 0.001] and improved neurological deficits [SMD = −6.39, 95% CI = (−9.091, −3.688), and p < 0.001]. SalA also significantly inhibited interleukin 6 (IL-6), tumor necrosis factor-a (TNF-α), IL-1β, and other indicators, such as Bcl-2-associated X protein (Bax) and Caspase-3 index, while showing a positive effect on B-cell lymphoma-2 (Bcl-2), Bcl-2/Bax, and other indicators.ConclusionThis meta-analysis demonstrates the therapeutic effects of SalA on IS. The results indicated that SalA significantly reduced the infarct area, improved neurological function scores, and alleviated brain edema. These effects were achieved through multiple mechanisms, including anti-inflammatory, antioxidative, antiapoptotic actions, along with blood–brain barrier (BBB) repair. SalA exhibited dose-dependent effects at different doses (especially 20 mg/kg) and administration methods. Further high-quality preclinical and clinical studies are needed for analysis.Systematic Review Registrationidentifier INPLASY2025110038